China's Puzzling Participation in the UN Peacekeeping Operations in Haiti - Chen, Jing (Asian perspective, 2024)
This article argues that positive US-China relations enabled China in 2004 to diversify its strategy toward Haiti, a staunch supporter of Taiwan, by contributing its first-ever Formed Police Unit (FPU) to the United Nations Stabilization Mission in Haiti (MINUSTAH). The organizational readiness of the China Peacekeeping Police Training Center (CPPTC) also played a large role in shaping this development. With the contribution of its FPUs, China intended to influence Haiti and reset bilateral relations. However, the limited training capacity of CPPTC meant that China could only contribute one FPU at a time—even though contributing more FPUs would have strengthened its influence on Haiti even more. When US-China relations turned negative and Zhou Yongkang, the chief patron of the Chinese police, lost power in 2012, China terminated its participation.